2009
DOI: 10.1002/jts.20442
|View full text |Cite
|
Sign up to set email alerts
|

Is posttraumatic stress disorder a stress‐induced fear circuitry disorder?

Abstract: Neuroimaging studies of posttraumatic stress disorder (PTSD) have reported functional abnormalities in brain regions involved in fear conditioning, extinction, and emotion regulation. These findings have prompted researchers to consider whether PTSD can be characterized as a stress-induced fear circuitry disorder. In this review, the authors summarize the results of functional neuroimaging studies and conclude that there is a strong argument for characterizing PTSD as a stress-induced fear circuitry disorder. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 84 publications
4
63
0
1
Order By: Relevance
“…This approach is based on the idea that PTSD may be generally linked to changes in the processing of emotional stimuli and not specifically to trauma-related stimuli. This view widens the possibility that PTSD involves not only fear conditioning, which has indeed been debated in the literature (Koenigs & Grafman, 2009;Shin & Handwerger, 2009).…”
Section: Processing Of Nontrauma-related Stimulimentioning
confidence: 96%
See 1 more Smart Citation
“…This approach is based on the idea that PTSD may be generally linked to changes in the processing of emotional stimuli and not specifically to trauma-related stimuli. This view widens the possibility that PTSD involves not only fear conditioning, which has indeed been debated in the literature (Koenigs & Grafman, 2009;Shin & Handwerger, 2009).…”
Section: Processing Of Nontrauma-related Stimulimentioning
confidence: 96%
“…To determine the risk factors for developing PTSD, Shin and Handwerger (2009) recently studied monozygotic twins who differed in their exposure to the Vietnam War. Veterans with PTSD and their twin brothers who were not exposed to war exhibited higher rates of cerebral glucose metabolism in the dorsal anterior/ midcingulate cortices compared with those without PTSD and their respective twins.…”
Section: Relationships Of Causality Between the Prefrontal-amygdala Cmentioning
confidence: 99%
“…A number of physiological differences are reported in persons with PTSD, including disturbances in neurological integration of the fear circuitry [34], reduced serotoninergic modulation of the fear response in key areas such as the amygdala [35], and dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis. Abnormal HPA axis function is often expressed by lower baseline cortisol levels and excessive suppression of the HPA axis by exogenous steroids [36][37][38].…”
Section: Initiating Effective Pharmacotherapymentioning
confidence: 99%
“…PTSD is considered a disorder of emotional memory that involves brain function abnormalities related to fear conditioning, fear memory extinction, involuntary retrieval (flashbacks and intrusions) and context-independent fear [6][7][8][9][10]. Numerous neuroimaging studies have reported diminished activation in the hippocampus in PTSD [11][12][13] or significant hippocampal volume reduction in PTSD patients [14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous neuroimaging studies have reported diminished activation in the hippocampus in PTSD [11][12][13] or significant hippocampal volume reduction in PTSD patients [14][15]. Similarly, the neurocircuitry models of PTSD posit that both hippocampal dysfunction and amygdala hyperactivity are related to the performance of emotional memory in PTSD [8,16]. If the hippocampus is not fully functional and does not form conscious emotional memories during a traumatic situation, it will form unconscious emotional memories that are supported by the amygdala [17].…”
Section: Introductionmentioning
confidence: 99%